2017
DOI: 10.1038/s41598-017-09499-1
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Foraging Optimization –Genetic Algorithm for Multiple Sequence Alignment with Multi-Objectives

Abstract: This research work focus on the multiple sequence alignment, as developing an exact multiple sequence alignment for different protein sequences is a difficult computational task. In this research, a hybrid algorithm named Bacterial Foraging Optimization-Genetic Algorithm (BFO-GA) algorithm is aimed to improve the multi-objectives and carrying out measures of multiple sequence alignment. The proposed algorithm employs multi-objectives such as variable gap penalty minimization, maximization of similarity and non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…Breast cancer is a common malignant tumor around the world. Genetic susceptibility and combined risk factors are main reasons for inducing breast cancer [1]. Cancer cell proliferation and epithelial-mesenchymal transition (EMT) are important factors of cancer recurrence.…”
Section: Introductionmentioning
confidence: 99%
“…Breast cancer is a common malignant tumor around the world. Genetic susceptibility and combined risk factors are main reasons for inducing breast cancer [1]. Cancer cell proliferation and epithelial-mesenchymal transition (EMT) are important factors of cancer recurrence.…”
Section: Introductionmentioning
confidence: 99%
“…However, to arrive at suitable alignment it is essential to control the length and number of gaps in an alignment. The three basic types of gap penalties are constant, linear and affine (Manikandan and Ramyachitra, 2017).…”
Section: Gap Penaltymentioning
confidence: 99%
“…It has been pointed out that the BFO algorithm can reduce the global convergence, computational burden, time and also handle a number of objective functions [39]. Comparisons with the conventional intelligent evolutionary computation algorithms, such as the Genetic Algorithm (GA) and Particle Swarm Optimization (PSO), have shown that BFO can realize a better optimization performance in many practical problems and real applications [40][41][42]. Considering the advantages of BFO over the conventional measures, it is adopted in this paper to evaluate the energy-efficient capability of the timetables.…”
Section: Bfo Algorithmmentioning
confidence: 99%